A composite strategy to prepare high active Pt-WO3/MWCNT catalysts for methanol electro-oxidation. (December 2021) - Guo, Dao-Jun; Cui, Shu-Kun
Abstract: Pt-WO3 /MWCNTao catalysts with high performance in methanol electro-oxidation were successfully synthesized in this paper. The structure and morphology of the catalysts were characterized by XRD and TEM techniques. The electrochemical activity of the as-prepared catalysts for methanol electro-oxidation was studied by cyclic voltammetry, CO-stripping and chronoamperometry, respectively. The results shown that the mass activity of Pt-WO3 /MWCNTao synthesized with two-step was promoted significantly; meanwhile, the CO oxidized potential was lower shift about 50 mV to 0.47 V. The super performance was proposed to be arising from the combination of the usage of high hydrophilic MWCNTs as the supports and employing the synergism effect of WO3 in methanol oxidation. And the nano-composites were proved to be a powerful and effective strategy to obtain anodic catalysts with super activity in direct methanol fuel cell. Highlights: The functionality of MWCNT surface with different treatment. The WO3 coating for super performance of Pt-WO3 /MWCNTao for methanol oxidation. The addition of WO3 enables to lower the onset potential of COad oxidation on Pt.